Beyond Translation Proper—Extending the Field of Translation Studies - Zethsen, Karen (TTR, 2007)
AbstractModern society demands many different kinds of translation or translation-like activities which often exceed the boundaries of what translation theory traditionally terms translation proper. Highly functional translations, localisation, précis-writing, expert-to-layman communication, etc. are all part of modern life, but where do such activities fit in theoretically? In this article I shall discuss the fact that despite Jakobson’s classical definition, intralingual translation or rewording is de facto peripheral to translation studies and I shall argue that the relationship between interlingual and intralingual translation is a neglected area of research, as is a thorough description of intralingual translation. Since Jakobson’s definition, general definitions of translation have become less inclusive. This I consider a major setback as there seems to be much to gain theoretically as well as practically by looking for similarities and differences between various kinds of translational activities. With the ulterior motive of putting intralingual translation (back?) on the map of translation studies and to encourage future empirical research within this area I shall argue for a broader perception of translation and consequently of translation studies as a discipline. Inspired by Jakobson (1959), Toury (1995) and Tymoczko (1998, 2005), I shall attempt to draw up an open definition of translation which reflects the many-faceted nature of the phenomenon.